Failure behaviour of grid-scored foam cored composite sandwich panels for wind turbine blades subjected to realistic multiaxial loading conditions. (September 2014) - Laustsen, S; Lund, E; Kühlmeier, L; Thomsen, OT
The load response and failure behaviour of 'grid-scored' sandwich panels used in wind turbine blades have been investigated. This paper presents the results of a combined experimental and numerical investigation of the load response and failure behaviour of a specific grid-scored foam cored composite sandwich panel configuration subjected to multiaxial quasi-static loading conditions that are representative for realistic loading conditions present in wind turbine blades. From the experimental evidence a criterion based on fracture mechanics has been proposed for predicting the onset of fracture in the resin grid. The criterion can be applied directly in conjunction with finite element modelling based on 3D solid elements where the resin grid in situ the core is fully modelled. However, since most full-scale blade models are based on first-order shear deformation theory where the core properties normally are homogenised a strain-based failure criterion is also proposed. The input for this failure criterion is the allowable resin grid strain, which can be obtained from a simple uniaxial tension test of a grid-scored sandwich beam specimen. The predictions of the criteria have been compared with the experimental observations, and a good correlation has been found.